Bunt czy egzaltacja? Atrybut młodości w literaturze popularnej na przykładzie wybranych powieści dla dziewcząt z okresu PRL-u - Bis, Katarzyna (Starość i młodość w literaturze i kulturze, 2016)
In this article author is writing about issues related with popular literature from a post II World Warperiod. Author of the paper by using as examples novels for girls is trying to characterise, find causes,manifestations and meaning of youthful rebellion described in those works. The article can continuea starting point for discussion, what exactly books for youths should contain and how powerful in theinfluence of weapon they are indeed in confrontation withfast developing young mind.